Occupational identities of management accountants: Situated identity regulation and work - Heinzelmann, Rafael (Proceedings of Pragmatic Constructivism, 2013)
This paper investigates occupational identities of management accountants. It casts light on the identity process consisting of identity regulation, work, and self-identity, wherein organizational identity regulation is drawn to the fore. To theorize this process, the paper draws on Alvesson and Willmott’s (2002) and on Giddens (1991). The accounting literature provides evidence that the role of accountants undergoes changes as a result of "new" technologies, competition, globalization and organizational managers’ demands (cf. Granlund and Lukka, 1998). This paper takes a different route by focusing on how one organization fosters the controlling of occupational identities. I argue in line with others, i.e. Morales and Lambert (2013), that accounting practices are constitutive for occupational identities. However, this relationship is not straightforward. It is characterized by the tension between the actual work and the professional ideals. In order to safeguard a consistent identity accountants engage in identity work. The results show that the combination of different means of identity regulation creates a strong repressive framework for accounting practices reducing the freedom to act and judge as a professional. It contributes to a better understanding of how accountants’ identities are subjected to control while simultaneously challenging the positive role associated with IT systems.